ANALISIS ISU-ISU MUAMALAT SEMASA DALAM BUKU AL-MU’AMALAT AL-MALIYYAH AL-MU’ASIRAH OLEH QAL’AHJI - Ibrahim, Basri (Jurnal Syariah, 2009)
Muamalah is an important element in a business entity and evolves from time to time. There are numerous issues that have emerged in this century and some of them were practiced by Islamic banks and there are also some of them that were elaborated by many outstanding ulama. One of the ulamas is Qal‘ahji in his work titled al-Mu‘amalat al-Maliyyah al-Mu‘asirah Fi Daw’i al-Fiqh Wa al-Shari‘ah. His elaboration on the issues of muamalah is very interesting based on the strength of its dalil and consideration to the public interest of the community (maslahah ummah), emergency situation as well as ijtihad ijma‘i performed by a few organizations of Academy of Fiqh Islam were taken accordingly.